Cognitive coping in relation to self-determination and quality of life in homeless young adults. (November 2018) - Altena, Astrid M.; Boersma, Sandra N.; Beijersbergen, Mariëlle D.; Wolf, Judith R.L.M.
Abstract: The purpose of this study was to explore the relationship between cognitive coping strategies and the experience of autonomy, competence, relatedness and quality of life in homeless young adults. The sample consisted of 251 young adults (age 18 to 25) who had just entered a Dutch shelter facility. In addition, moderating effects of cognitive coping in the relationship between life stressors and the outcomes were examined. The analyses were conducted by means of linear regression. Our results indicated that adaptive cognitive coping strategies were related to the constructs of self-determination. Both adaptive and maladaptive cognitive coping strategies were related to quality of life. Positive reappraisal and positive refocusing moderated the relationship between life stressors and the outcomes. The implications of interventions will be discussed. Registration: Dutch trial register (registration number NTR3254), (http://www.trialregister.nl/trialreg/admin/rctview.asp?TC=3254 ). Highlights: Adaptive cognitive coping is related to self-determination in homeless young adults. Adaptive and maladaptive cognitive coping is related to quality of life. Positive reappraisal and positive refocusing buffer against stressors.